2015
DOI: 10.1093/cvr/cvv282
|View full text |Cite
|
Sign up to set email alerts
|

Omentin attenuates atherosclerotic lesion formation in apolipoprotein E-deficient mice

Abstract: These data document for the first time that omentin reduces the development of atherosclerosis by reducing inflammatory response of macrophages through the Akt-dependent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 42 publications
4
59
0
1
Order By: Relevance
“…Omentin also inhibits growth factor-induced smooth muscle cell migration through the anti-oxidative mechanism 79) . More recently, we have shown that omentin attenuates atherosclerotic lesion formation in a mouse model of atherosclerosis 80) . Therefore, omentin acts as an adipocytokine that protects against vascular injury (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Omentin also inhibits growth factor-induced smooth muscle cell migration through the anti-oxidative mechanism 79) . More recently, we have shown that omentin attenuates atherosclerotic lesion formation in a mouse model of atherosclerosis 80) . Therefore, omentin acts as an adipocytokine that protects against vascular injury (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Omentin-1 transgenic (OMT-Tg) mice on an ApoE-KO background (ApoE-KO/ OMT-Tg mice) exhibited attenuated atherosclerotic areas in the aortic sinus compared with ApoE-single KO mice. 58 ApoE-KO/OMT-Tg mice manifested significantly reduced macrophage infiltration and expression of pro-inflammatory cytokines (such as TNF-α, IL-6 and monocyte chemoattractant protein 1) in the aorta compared with ApoE-KO mice. In human monocyte-derived macrophages, omentin-1 protein significantly reduced lipid droplets and cholesteryl ester contents.…”
Section: Omentin-1mentioning
confidence: 90%
“…In vitro, omentin-1 has been shown to suppress TNFα-induced inflammatory responses in vascular endothelial cells via an AMPK-eNOS pathway 342 . More recently, omentin overexpression has been reported to attenuate atherosclerosis in hyperlipidemic mice 343 . Overall, it is plausible that low levels of omentin-1 can contribute to the development of CV dysfunction in obese individuals.…”
Section: Cardiovascular Actions Of Select Adipokinesmentioning
confidence: 99%